Vocabulary and language skills acquisition using translated historical fiction in young learners of english as a foreign language. - Nazareno Delgado, Karla Cecilia (2025)
The purpose of this research was to integrate Ecuadorian literature in the EFL classroom through the translation of selected chapters of the historical fiction book, Horacio, el ferrocarril y las esterlinas desaparecidas, to be used as instructional material among middle grade students to enhance their vocabulary acquisition skills. The translation utilized the communicative approach to ensure readability in the target readership, and several excerpts from the book were analyzed to prove the efficacy of said method. Additionally, a website was built, allowing students to access the selected chapters as well as interactive post-reading activities. By translating a local book into English, this research highlights the potential of literature-based instruction as an effective tool for vocabulary acquisition. Therefore, it supports the development of engaging, culture-rich pedagogical resources that bridge linguistic and historical knowledge, reinforcing the value of incorporating Ecuadorian literature in EFL curricula.